Manhaj and Style of Interpretation of Ali As-Shobuni in Rawa'i Al-Bayan and Shofwa At-Tafasir - Yogi ilham; Syafruddin, Syafruddin; Radhiatul Hasnah (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the exegetical methodology (manhaj) employed by Muhammad Ali ash-Shabuni in his two monumental works, Shafwah al-Tafāsīr and Rawā’i al-Bayān. The research focuses on the methods, characteristics, and interpretive orientations that distinguish these two tafsirs, as well as their contribution to the development of contemporary Qur’anic studies. This study uses a qualitative-descriptive approach through library research and content analysis of the primary tafsir texts. The findings show that Shafwah al-Tafāsīr is written using the tahlīlī method, combining tafsīr bi al-ma’tsūr (interpretation based on transmitted reports) and tafsīr bi al-ra’yi (interpretation based on rational reasoning). Its exegetical style is adabī ijtimā‘ī, emphasizing moral, social, and ethical messages to make the Qur’an more accessible to modern readers. Meanwhile, Rawā’i al-Bayān represents a fiqhī (legal) tafsir focused on āyāt al-aḥkām (legal verses) through a systematic process consisting of linguistic analysis, examination of asbāb al-nuzūl, comparative study of classical legal schools, and elaboration of ḥikmah al-tashrī‘ (philosophy of Islamic law). These two works demonstrate ash-Shabuni’s effort to bridge classical scholarship with contemporary needs, offering interpretations that are concise, academic, and relevant.